Use of Quality and Organic Pollution Indices in The Physico-Chemical Quality Assessment of Kébir Wadi East Surface Waters (Region of El Taref, Extreme North East Algeria) - Bahroun, Sofia; Nouri, Nada; Smida, Bouthaina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Surface water is subject to strong anthropogenic pressures caused by the development and the extension of the agricultural activities and also by the industrial and domestic activities. Pollution is a major environmental problem due to discharges into rivers and the excessive use of agricultural fertilizers add to that the discharges from urban and industrial sources.
Keywords: surface water; water quality index (WQI); organic pollution index (OPI); urban wastes; seasonal variation; North East Algeria; Kébir wadi East; wody powierzchniowe; wskaźnik jakości wody; wskaźnik zanieczyszczenia organicznego; odpady miejskie; Algieria północno-wschodnia